HISTORY CREATED: LIM CHEE WEI WINS 2014 MASUM’S SPORTSMAN AWARD - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 4 April 2015 National karate exponent and 2014 Asian Games gold medallist Lim Chee Wei created history by becoming the first Universiti Sains Malaysia (USM) student to be crowned the Malaysian Universities Sports Council (MASUM) Sportsman for 2014.